EFFECT OF BOVINE EMBRYO PRODUCTION BY IN VITRO FERTILIZATION OF FRESH AND CRYOPRESERVED OOCYTES WITH CRYOPRESERVED SPERMS - Ngọc, Phan Kim (Vietnam Journal of Biotechnology, 2011)
Bovine embryo production is an important measure to proliferate cows, especially for milk cows. The oocytes used in embryo production usually were those fresh derived from cows ultrasound guided follicle aspiration, fresh oocytes derived from ovary aspiration or cryopreserved. This research aimed to compare efficiency of bovine embryo production by in vitro fertilization of fresh oocytes derived from ulfrasound guided follicle aspiration (abbreviation: ultrasounded oocytes), fresh oocytes derived from ovary aspiration (abbreviation: slaughter-house oocytes), and cryopreserved oocytes (good grade oocytes derived from ovary aspiration were cryopreserved, and thawed before use). Cryopreserved sperms were used to inseminate oocytes. Efficiency infertilization was based on ratio of 2-cell embryo formed. Efficiency of embryo development was based on ratio of 8-cell embryos, morula embryos, and blastocysts. The results showed that highest efficiency of infertilization was of ultrasounded oocytes with cryopreserved sperms, and lowest of cryopreserved oocytes. In the experiment with ultrasounded oocytes, there were 47.93% of infertilized oocytes forming 8-cell embryos, 41.20% of momla embryos, and 27.32% of blastocyst embryos; while there were 34.13, 23.06, and 18.01% in the experiment with slaughter-house oocytes, 11.67, 9.95, and 5.37% in the experiment with cryopreserved oocytes, respectively.